Pengendalian Persediaan Bahan Baaku Kedelai Yang Optimum dalam Produksi Keripik Tempe di Usaha Keripik Tempe Sanan Malang - Mufriantie, Fithri; Tain, Anas; Febrianti, Berta Dwi (Universitas Galuh, 2024)
Tempeh Chips is an industry engaged in agro-industry that uses soybeans as raw material for making tempeh chips. One of the important factors in the production process is raw material inventory. The purpose of this study was to determine the optimum and economical amount of raw material purchases, the amount of raw material inventory and the right time to reorder. This research was conducted in Purwantoro Village, Blimbing District, Malang City. The sampling technique was done intentionally. The data used in this study are primary data and secondary data. The analysis method used is Economic Order Quantity (EOQ) analysis and using the POM-QM For Windows V.5.3 application. The results of this study indicate that the optimal and economical purchase of soybean raw materials for each purchase is 32 Kg. The required Safety Stock is 75 Kg, Re-Order Point is done if the remaining soybean raw material inventory is 104 Kg. Controlling raw material inventory using the EOQ method is more efficient, so companies can consider using the EOQ method in controlling raw material inventory.